Philosopher in space and time of culture (chronotope of maître à penser). Part II - M. M. Rohozha, (Ukrainian Cultural Studies, 2018)
The paper deals with the research of philosophic way of life as an invariant of the Western culture. The author tries to reveal the answers to the questions: What is the influence of the time and place of life on a thinking person? Is it possible to put a question in such a way? The second part of the paper gives methodological explanation for such putting the questions. Two conceptual strategies of thinking in the contemporary history of philosophy are mentioned – compartmentalism and biographical method. The latter one allows understanding of the philosophizing through research of maître à penser. Such approach made possible cultural studies prospect for a philosopher’s life in the context of unique time and space. To designate the uniqueness of time and space, the category of chronotope (M. Bakhtin) was introduced in the paper. Chronotope sets condensed signs in a definite period of time at the result of which a unique image of a thinker is born in a definite cultural space. Uniqueness of time and space sets originality of philosophical quest of a thinker. Analysis of one’s philosophizing through the prism of one’s life allows us to compare proved and practiced dimensions, and affirm a status of “maître à penser”, if these dimensions are coincided. The second part of the paper is focused on the time and space of the epoch of Modernity, where public space of the city as a place of activity for a philosopher is inseparably linked to critically directed an self-organized general public. Special attention is focused on life activity of Albert Schweitzer and Hannah Arendt. The author concludes that unlike Antiquity and Middle Ages where we were focused on the images of philosophers, Modernity deals with personalities of philosophers. Schweitzer as well as Arendt personally testify to their life and philosophical practice. The point is that definite life experience according to personal philosophy is purely important moral milestone, transforming the person to worthy exemplary.
Keywords: philosopher, public sphere, general public, scientist, maître à penser, Albert Schweitzer, Hannah Arendt, service to people, Western intellectual tradition, spiritual exercises